Pengaruh Terapi Dzikir Terhadap Intensitas Nyeri pada Pasien Post Operasi Ca Mammae di Rsud Prof Dr Margono Soekarjo Purwokerto - Toni Budiyanto; Atun Raudotul Ma’rifah; Paulina Irma Susanti (Jurnal Keperawatan Maternitas, 2015)
One of The problems occuring on post surgical is the pain patients felt due to the wounds of surgery. After the effect of the anesthesia disappears the patients will feel pain in the area of the breast after mastectomy. This would lead to the comfortable feeling, restless, nervous, and other various disorders of mood or feelings.. When a person is confronted to a state that is likely to cause feeling depressed, they will desperately need a compensation so thet such perceived feelings can be addressed.The purpose of the study was to identify The Effect of Dzikir the Therapy to the Pain Intensity on Mammae Cancer Post Surgical Patients in RSUD Prof Dr. Margono Soekarjo Purwokerto.The study was pre experiment whit one group pretest and posttest design. The sampling technique used was accidental sampling and the sample of this study were all mammae cancer post surgical patients.The result of the study shows thet was average pain prior to treatment was 7.80 with the lowest pain was 7 and the highest was 9. The average pain after the treatment was 3.32 with the lowest was 2 and the highest was 6. There is the effect of dzikir therapy to the pain intensity on Mammae Cancer Post Surgical Patients before and after given the terapy with p-value 0.000, p-value < α (0,000 < 0,05).In conclusion, dzikir therapy very useful to decrease pain of intensity on Mammae Cancer Post Surgical Patients in addition to pharmacological therapy.